A retrospective real-world study of early short-course remdesivir in non-hospitalized COVID-19 patients at high risk for progression: low rate of hospitalization or death, regardless of immunocompetence status - Ramos-Rincón, José Manuel; Pinargote-Celorio, Héctor; Llenas-García, Jara; Moreno-Pérez, Oscar; González-Cuello, Inmaculada; Gonzalez-de-la-Aleja, Pilar; Martínez-López, Belén; Reus, Sergio; García-López, María; Rodríguez, Juan Carlos; Boix, Vicente; Merino, Esperanza (Frontiers in Pharmacology, 2023)
Introduction: The evidence for remdesivir therapy in immunocompromised patients is scarce. To evaluated remdesivir (RDV) effectiveness and safety in COVID-19 outpatients at high risk for progression in a real-world setting. We compare the outcome in immunocompromised (IC) and with non-immunocompromised patients. Methods: Two hospitals retrospective study of all adult patients with mild-to-moderate SARS-CoV-2 infection at high risk for disease progression that were treated as out-patients with a 3-day course of RDV (1st January -30th September 2022). The primary effectiveness end point was a composite of any cause hospitalization or death by day 30. A Multiple logistic regression model was built to explore the association between immune status and clinical outcome, estimating adjusted odds ratios (aORs [95% CI]). Results: We included 211 patients, 57% males, median age 65 years (IQR 53-77), 70.1% vaccinated (>2 doses) and 61.1% IC. The median duration of symptoms before RDV treatment was 3 days (IQR 2-5). During follow up 14 (6.6%) were hospitalized, 6 (2.8%) for COVID-19 progression. No patient required mechanical ventilation, and two patients died (non-COVID19 related). After accounting for potential confounders, only anti-CD20 treatment was associated with the composed outcome (aOR 5.35[1.02-27.5, 95%CI]), whereas immunocompetence status was not (aOR 1.94[0.49-7.81, 95%CI]). Conclusion: Early COVID-19 outpatient treatment with a 3-day course of remdesivir in vaccinated patients at high-risk for disease progression during Omicron surge had a good safety profile. It was associated with low rate of all-causes hospitalization or death, regardless of immunocompetence status.